2018
DOI: 10.1371/journal.pone.0196163
|View full text |Cite
|
Sign up to set email alerts
|

Changes in N-glycans of IgG4 and its relationship with the existence of hypocomplementemia and individual organ involvement in patients with IgG4-related disease

Abstract: BackgroundAlthough increased serum IgG4 level and tissue infiltration of IgG4-positive cells are key events in IgG4-related disease (IgG4RD), and nearly half of IgG4RD patients show hypocomplementemia, the role of IgG4 in the pathogenesis of IgG4RD remains unclear. Many reports show that altered IgG glycosylation, especially IgG with agalactosylated N-linked glycan (G0 N-glycan), have proinflammatory roles including complement activation, implicated in the pathogenesis of various inflammatory diseases. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 70 publications
2
20
0
Order By: Relevance
“…32 Recently, a small study reported increased IgG4 G0 N-glycans and IgG4 fucosylated N-glycans in patients with IgG4-RD (n = 12) compared with HCs (n = 8), with IgG4 non-fucosylated N-glycans decreased in those with hypocomplementaemia (n = 7). 33 In line with this, we found a negative correlation between C3 and C4 levels and both IgG4 fucosylation, and IgG1/2/3 hybrid structures. The relevance of this remains uncertain, given that fucosylation and galactosylation are primary mediators of functional changes in IgG for FcγR-mediated and complement-mediated effector functions, respectively.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…32 Recently, a small study reported increased IgG4 G0 N-glycans and IgG4 fucosylated N-glycans in patients with IgG4-RD (n = 12) compared with HCs (n = 8), with IgG4 non-fucosylated N-glycans decreased in those with hypocomplementaemia (n = 7). 33 In line with this, we found a negative correlation between C3 and C4 levels and both IgG4 fucosylation, and IgG1/2/3 hybrid structures. The relevance of this remains uncertain, given that fucosylation and galactosylation are primary mediators of functional changes in IgG for FcγR-mediated and complement-mediated effector functions, respectively.…”
Section: Discussionsupporting
confidence: 87%
“…In a US cohort, reduced C3 (20%), C4 (19%), or both (11%) were present in 103 IgG4‐RD patients and were associated with a more inflammatory phenotype, higher serum IgG4 levels, and IgG4‐related kidney involvement . Recently, a small study reported increased IgG4 G0 N‐glycans and IgG4 fucosylated N‐glycans in patients with IgG4‐RD ( n = 12) compared with HCs ( n = 8), with IgG4 non‐fucosylated N‐glycans decreased in those with hypocomplementaemia ( n = 7) . In line with this, we found a negative correlation between C3 and C4 levels and both IgG4 fucosylation, and IgG1/2/3 hybrid structures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sugimoto et al [84] have analyzed the PEG-precipitated IC from IgG4-RD patients and found that IgG4 could participate in the activation of complements in IgG4-RD patients with hypocomplementemia. To elucidate the inconsistency in complement-activating effect of IgG4 antibody, Konno et al [85] have analyzed the N-linked glycan of IgG4 molecule derived from patients with IgG4-RD. They found decreased galactosylation of IgGs is irrelevant to complement activation whereas IgG4 fucosylation may lead to complement activation, hypocomplementemia and various organ damages in patients with IgG4-RD.…”
Section: The Glycosylation Patterns Of Igg4 Molecule Induce Complemenmentioning
confidence: 99%
“…In particular, as detected by Sambucus nigra agglutinin (SNA) affinity chromatography, the presence of variable domain sialylation was increased in both IgG1 and IgG4 subclasses, even when corrected for the inherently higher N-linked glycosylation rates in IgG4 variable regions (46). This observation was corroborated by another study investigating combined variable domain and Fc-glycosylation in IgG4-RD patients (44). Although the role of increased variable domain glycosylation is unclear, it is suggested that increased variable domain sialylation could impart IgG4 immunoglobulins in the context of IgG4-RD with disease-specific immunomodulatory properties through binding of SIGLECs such as CD22 (62).…”
Section: Immunoglobulin G4-related Diseasementioning
confidence: 62%